2015
DOI: 10.1146/annurev-resource-100913-012639
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of the International Trade of Waste

Abstract: International trade in hazardous and nonhazardous waste and scrap products has been growing at an exceptional rate the past two decades. This review presents current data on the magnitude and trends regarding this growth and discusses the recent literature as it pertains to the economic incentives and drivers of international waste trade. Differences in environmental policy, taxes, disposal fees, and transport costs are important determinants across countries. However, the illegal nature of many types of hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Research has also found that a large portion of the trade in waste is south-south (ref) but that the majority of trade in hazardous waste is north-north [18,22]. The increasing trade in eWaste and the distinction under the Basel Convention between waste and non-waste is currently also a focal point for the Secretariat of the Basel Convention [23].…”
Section: At the International Level The Agreement With The Greatest mentioning
confidence: 99%
“…Research has also found that a large portion of the trade in waste is south-south (ref) but that the majority of trade in hazardous waste is north-north [18,22]. The increasing trade in eWaste and the distinction under the Basel Convention between waste and non-waste is currently also a focal point for the Secretariat of the Basel Convention [23].…”
Section: At the International Level The Agreement With The Greatest mentioning
confidence: 99%
“…Among researchers and policymakers, expanding global trade and investment has become the fuel that drives concerns of environmental sustainability caused by the flow of production factors across borders. According to Kellenberg [1], wastes trade in 2012 was approximately 500% greater in size compared with two decades earlier and is becoming a crucial component of global factor flows [2]. Dominated by concerns of environmental pollution [3] and illegal dumping [4] through traded wastes, the literature remains concentrated on developed countries such as the United States and those in the European Union, while waste trade in developing countries has received limited attention [5].…”
Section: Introductionmentioning
confidence: 99%
“…The global trade of waste and scrap is becoming increasingly a flow of waste from developed to developing countries, growing 500% over the two decades since 1992 (Kellenberg, 2015). Proponents of the waste trade maintain that importers can benefit by gaining access to cheap, recycled input materials.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first econometric analysis of the impact of OGF on the international waste trade. More generally, there are few studies that examine the international waste trade specifically; Kellenberg (2015) reviews the literature. Kellenberg and Levinson (2014) study the impact on countries ratifying a multilateral agreement seeking to regulate the international waste trade, ‘The Basel Convention on the Control of Transboundary Movements of Hazardous Waste and their Disposal’.…”
Section: Introductionmentioning
confidence: 99%